Liver function may play an uneven role in haemorrhagic transformation for stroke subtypes after acute ischaemic stroke. (20th November 2015) - Tan, G.; Lei, C.; Hao, Z.; Chen, Y.; Yuan, R.; Liu, M.
Abstract : Background and purpose: Haemorrhagic transformation (HT) is common after acute ischaemic stroke. Whether liver function plays a role in HT remains an open question. Methods: Acute ischaemic stroke patients within 7 days from stroke onset were included. Baseline data including liver function tests were collected. An independent association between liver function and HT was identified by multivariate regression analysis for stroke overall and stroke subtypes. Results: A total of 2788 patients were included. HT occurred in 277 patients (9.9%), with 32 patients (1.1%) with symptomatic HT and 245 patients (8.8%) with asymptomatic HT. On multivariate regression analysis, aspartate aminotransferase (AST) and bilirubin (BILI) were independently associated with HT for stroke overall. In different stroke subtypes, AST was independently associated with HT for cardioembolic stroke, BILI for stroke of undetermined aetiology, and no liver function indicators for stroke of large‐artery atherosclerosis and small‐artery occlusion. Conclusions: Liver function played an uneven role in HT for different stroke subtypes. Indicators of liver function independently associated with HT were AST for cardioembolic stroke, BILI for stroke of undetermined aetiology and none for stroke of large‐artery atherosclerosis and small‐artery occlusion.